Destination Management Organization (DMO) in Indonesia, an overview and should be continue? - Putra, Dewa Putu Bagus Pujawan (Journal of Applied Science in Tourism Destination, 2024)
The research aim to evaluate Destination Management Organization (DMO) program in Indonesia which initiate by Ministry of Tourism and Creative Economy (2011-2014) and what the next for the future of tourism especially to achieve quality and sustainable tourism. Using desk research to collect information and data from DMO in Indonesia and interviewed with key person to analyze and summarize the main things which vital points to manage destination as per international standards from United Nations of World Tourism Organization (UNWTO). The research found active community participation as a vital point and Indonesia need local champion to continuously assist the destination to be grew with strategic leadership, effective execution and efficient governance for sustainable and quality tourism. Further studies and research in tourism destination should conduct to adapt and summarize critical factor for resources/capital and marketing then the destination could captive the ideal market and distribute its benefit among stakeholder. Because tourism destination will be sustain and quality if environmental preserved, socio-cultural protected and economic prosperity fairly distribute among stakeholder.